Tissue Engineering and Its Potential to Reduce Prostate Cancer Treatment Sequelae—Narrative Review - Adamowicz, Jan; Kluth, Luis Alex; Pokrywczynska, Marta; Drewa, Tomasz (Frontiers in Surgery, 2021)
Tissue engineering offer possibility to overcome limitations of current management for postprostatectomy incontinence and ED. Developed in recent years biotechnological feasibility of mesenchymal stem cell isolation, in vitro cultivation and implantation became the basis for new cell based therapies oriented to induce regeneration of adult tissue. The perspective to offer patients suffering from post-prostatectomy incontinence or erectile dysfunction minimal invasive one-time procedure utilizing autologous stem cell transplantation is desired management.